2014
DOI: 10.1108/jpif-10-2013-0063
|View full text |Cite
|
Sign up to set email alerts
|

Integration between real estate equity and non-real estate equity

Abstract: Purpose – The paper examined the long-run relationship between real estate equity (property listed stock) and non-real estate equity (common stock) in the Nigerian capital market and established the integration between the investments. The paper aims to discuss these issues. Design/methodology/approach – The data collected comprised quarterly returns on property listed stock and All Share Index for the period of January 1999-December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
5
14
0
Order By: Relevance
“…The findings were reported in literatures and past studies (Hamzah and Rozali, 2010;Liow and Adair, 2009;Newell et al, 2013;Newell and Osmadi, 2009;Ong et al, 2012). Few studies have investigated Nigerian real estate securities and property market (Amidu and Aluko, 2006;Amidu et al, 2008;Olaleye and Ekemode, 2014).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The findings were reported in literatures and past studies (Hamzah and Rozali, 2010;Liow and Adair, 2009;Newell et al, 2013;Newell and Osmadi, 2009;Ong et al, 2012). Few studies have investigated Nigerian real estate securities and property market (Amidu and Aluko, 2006;Amidu et al, 2008;Olaleye and Ekemode, 2014).…”
Section: Introductionsupporting
confidence: 52%
“…The study could not assess the N-REIT performance due to lack of trading data to compute index series for the Nigeria REIT. Other studies that has studied real estate securities in Nigeria did not include REIT in their studies (Amidu et al, 2008 andOlaleye andEkemode, 2014). The Nigerian economy is the largest in the African continent with growth rate of 8.5% and has established REIT regime for 8 years.…”
Section: Introductionmentioning
confidence: 99%
“…The study noted that indirect real estate asset underperformed most other assets on the basis of mean variance ratio and showed no diversification benefits when combined with other assets. While Olaleye and Ekemode (2014) investigated the long run association between public real estate and common stocks in the Nigerian capital market from 1999 to 2011. The study showed that SP outperformed stocks with a corresponding higher risk level.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…In the same vein, Ntuli and Akinsomi (2017) found that South African REITs are good returnenhancers. In Nigeria, relevant performance studies on real estate investments included the studies carried out by Ogunba (2013), Olaleye and Ekemode (2014) among others. However, no study so far to be best of the authors' knowledge have looked at the impact of inflation on Nigerian indirect real estate investments such as Nigerian REITs and non REITs equities.…”
Section: Introductionmentioning
confidence: 99%